2014
DOI: 10.1371/journal.pone.0112674
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sequencing of HIV-1 near Full-Length Proviral Genomes Identifies High Rates of BF1 Recombinants Including Two Novel Circulating Recombinant Forms (CRF) 70_BF1 and a Disseminating 71_BF1 among Blood Donors in Pernambuco, Brazil

Abstract: BackgroundThe findings of frequent circulation of HIV-1 subclade F1 viruses and the scarcity of BF1 recombinant viruses based on pol subgenomic fragment sequencing among blood donors in Pernambuco (PE), Northeast of Brazil, were reported recently. Here, we aimed to determine whether the classification of these strains (n = 26) extends to the whole genome sequences.MethodsFive overlapping amplicons spanning the HIV near full-length genomes (NFLGs) were PCR amplified from peripheral blood mononuclear cells (PBMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…The near full-length genomes and/or larger fragments of the 45 V3 MPS data used in this study have recently been described for their genetic variability [ 23 ]. This analysis indicated that 28 (62.2 %) were subtype B sequences, 11 (24.4 %) BF1 recombinants, 2 (4.4 %) BC recombinants, 1 (2.2 %) were BC and BCF1 each, 1 (2.2 %) CRF45_cpx, and 1 (2.2 %) were the newly described CRF70_BF1 [ 30 ]. The tropism predictions, FPR values, and V3 net charges are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The near full-length genomes and/or larger fragments of the 45 V3 MPS data used in this study have recently been described for their genetic variability [ 23 ]. This analysis indicated that 28 (62.2 %) were subtype B sequences, 11 (24.4 %) BF1 recombinants, 2 (4.4 %) BC recombinants, 1 (2.2 %) were BC and BCF1 each, 1 (2.2 %) CRF45_cpx, and 1 (2.2 %) were the newly described CRF70_BF1 [ 30 ]. The tropism predictions, FPR values, and V3 net charges are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…As a comparative method, we applied the simple quality-filtering correction method reported by others (Dudley et al, 2012 ; Gall et al, 2012 ; Pessoa et al, 2014 ) to the same pNL4-3 wt sequence reads. The quality-filtering method simply discards any nucleotides with a QS below 20 or 30 as a cut-off value (Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The former subtype I is likewise a recombinant virus (CRF04_cpx) and therefore no longer contained in the A-K grouping. Up to now, more than 70 different epidemiologically stable CRF have been described [8,14,15,16], and the development of additional CRF is to be expected.…”
Section: Current Knowledge About the Pathogenmentioning
confidence: 99%
“…In addition to HIV-1 M:B (and especially the Brazilian subtype Bb), HIV-1 M:A, A/E (CRF01_AE), C and F are prevalent [96]. Further recombinants are found in Brazil and in neighbouring countries [16]. Two other recombinant strains of the subtypes B and F (CRF12_BF and CRF17_BF) are circulating in Argentina [110].…”
Section: Current Knowledge About the Pathogenmentioning
confidence: 99%